Preparation method of self-curing tundish dry material

By mixing, forming, drying, sintering, cooling and grinding in the preparation process of the slack material, combined with layered filling, vibration treatment, degassing and curing treatment, the problem of insufficient curing strength of the slack material is solved, and the high strength and high quality of the refractory layer are achieved.

CN119658804AActive Publication Date: 2025-03-21TANGSHAN GUOLIANG SPEICAL REFRACTORY MATERIAL

Patent Information

Application Number
CN202510181025.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

In the prior art, the adjustment of grinding power and vibration parameters are missing when preparing the cushioned raw material, resulting in the curing strength of the cushioned raw material being unable to meet the curing needs.

Method used

By mixing, forming, drying, sintering, cooling and grinding the raw materials of the slaughtered raw materials, the slaughtered raw materials are prepared and mixed with the gel material to form a refractory bulk material. Then, layered filling and vibration treatment are adopted, combined with degassing and curing treatment, the curing strength and pore area ratio of the cured refractory layer are detected, and the vibration parameters or grinding power are adjusted according to actual conditions to meet the standard curing strength requirements.

Benefits of technology

Optimize the particle size of the cushioned and grinding, improve the overall strength and durability of the refractory layer, and improve the airtightness and thermal stability through layered filling and vibration treatment, ensuring consistency of product quality and controllability of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119658804A_ABST
    Figure CN119658804A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to a preparation method of a self-curing tundish dry material, which comprises the following steps of: mixing, forming, drying, sintering, cooling and grinding raw materials of the tundish dry material, and mixing the obtained tundish dry material bulk material and a gel material according to a preset proportion; the tundish mold is filled with the fireproof bulk materials obtained through mixing, layered filling is adopted, vibration and degassing treatment are conducted on each layer of fireproof bulk materials to obtain a degassed fireproof solid material, curing treatment is conducted on the degassed fireproof solid material to obtain a cured fireproof layer, and the curing strength of the cured fireproof layer is detected to obtain the actual curing strength; and for the condition that the actual curing strength cannot meet the standard curing strength requirement, the standard curing strength requirement is met by adjusting vibration parameters or adjusting grinding power. By adjusting the grinding power and the vibration parameters, the curing strength of the self-curing tundish dry material meets the curing requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a method for preparing self-solidifying tundish dry material. Background Art

[0002] Tundish dry material is a refractory material used in high temperature environments. It is usually used as a coating or isolation layer in the steel smelting process to protect the tundish from the erosion of high temperature slag and molten steel.

[0003] China Patent Publication No.: CN117776699A discloses an environmentally friendly dry material for a tundish and a preparation method thereof, comprising the following steps: adding forsterite aggregate ①, forsterite aggregate ②, fused magnesia powder, environmentally friendly binder, admixture and silicon powder into a mixer, and mixing them evenly in the mixer to obtain an environmentally friendly dry material. The environmentally friendly dry material for a tundish is prepared by mixing forsterite as aggregate, fused magnesia as fine powder, and adding an appropriate amount of non-resin binder and admixture.

[0004] It can be seen that the prior art has the following problems: due to the lack of adjustment of grinding power and vibration parameters when preparing the dry material in the tundish, the solidification strength of the dry material in the tundish cannot meet the solidification requirements. Summary of the invention

[0005] To this end, the present invention provides a method for preparing a self-curing tundish dry material, so as to overcome the problem in the prior art that the curing strength of the tundish dry material cannot meet the curing requirements due to the lack of adjustment of grinding power and vibration parameters when preparing the tundish dry material.

[0006] To achieve the above object, the present invention provides a method for preparing a self-curing tundish dry material, comprising the following steps:

[0007] The tundish dry material raw materials are mixed, formed, dried, sintered, cooled and ground to obtain tundish dry material bulk, and the tundish dry material bulk and gel material are mixed according to a preset ratio to obtain refractory bulk;

[0008] Filling the refractory bulk material into a tundish mold, and adopting layered filling, vibrating each layer of the refractory bulk material to obtain a refractory solid material, degassing the refractory solid material to obtain a degassed refractory solid material, curing the degassed refractory solid material to obtain a cured refractory layer, and detecting the curing strength of the cured refractory layer to obtain an actual cured strength;

[0009] In the case where the actual curing strength cannot meet the standard curing strength requirement, the standard curing strength requirement is met by adjusting the vibration parameters or the grinding power;

[0010] The vibration parameters include vibration frequency and vibration duration.

[0011] Further, the process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes:

[0012] The curing strength of the cured refractory layer is tested by compressive strength test to obtain the actual curing strength. If the actual curing strength cannot be determined by a single test, the pore area on the surface of each layer of degassed refractory solid material is tested to obtain the actual pore area ratio of the degassed refractory solid material;

[0013] The actual pore area ratio is the ratio of the pore area in the detection area to the area of ​​the detection area.

[0014] Further, the process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes:

[0015] The actual pore area ratio of each layer of degassed refractory material is compared with the standard pore area ratio range to obtain a first area ratio comparison result, and the solidified refractory layer in the corresponding layered area is selected according to the first area ratio comparison result for a solidification strength test.

[0016] Further, the process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test according to the first area ratio comparison result includes:

[0017] If the first area ratio comparison result shows that the actual pore area ratio is not within the standard pore area ratio range, select the cured refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual cured strengths to be verified, compare the actual cured strengths to be verified with the standard cured strength range to obtain a first cured strength comparison result, and determine whether to adjust the grinding power, curing time, vibration parameters or vibration mode according to the first cured strength comparison result;

[0018] Wherein, the standard curing strength interval is determined according to the standard curing strength.

[0019] Further, the process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual solidified strengths to be verified includes:

[0020] For stratified regions where the actual pore area ratio is less than the minimum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified region to obtain a first actual cured strength to be verified; for stratified regions where the actual pore area ratio is greater than the maximum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified region to obtain a second actual cured strength to be verified.

[0021] Further, the process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes:

[0022] Compare the first actual curing strength to be verified with the standard curing strength range. If the comparison result of the first curing strength is that the first actual curing strength to be verified is not within the standard curing strength range, increase the grinding power or reduce the degassing time to meet the standard curing strength requirement.

[0023] Further, the process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes:

[0024] The second actual curing strength to be verified is compared with the standard curing strength interval. If the comparison result of the first curing strength is that the second actual curing strength to be verified is not within the standard curing strength interval, the vibration frequency is adjusted to meet the standard curing strength requirement.

[0025] Further, the process of adjusting the vibration frequency to meet the standard curing strength requirement includes,

[0026] If the vibration frequency cannot meet the standard curing strength requirement, the vibration duration can be adjusted to meet the standard curing strength requirement.

[0027] Furthermore, the refractory bulk material is filled into the tundish mold, and the process of layered filling includes:

[0028] The thickness of the first layer of the filling bulk material is determined according to the grinding particle size of the dry bulk material in the tundish, and the vibration duration is determined according to the thickness of the first layer of the bulk material.

[0029] Further, the process of adjusting the vibration frequency to be unable to meet the standard curing strength requirements includes:

[0030] While keeping the vibration frequency unchanged, adjust the vibration mode to meet the standard curing strength requirements;

[0031] Wherein, the vibration mode includes vertical vibration and horizontal vibration.

[0032] Compared with the prior art, the beneficial effect of the present invention is that, through sintering and grinding operations, the particle size of the tundish dry bulk material is optimized, the contact area and connection strength between the particles are increased, thereby enhancing the overall strength and durability of the refractory layer. Layered filling and vibration treatment help to remove air from the refractory bulk material, reduce pores, and improve density, thereby improving the air tightness and thermal stability of the refractory layer. Vibrating the refractory bulk material in the mold by mechanical vibration can quickly and effectively remove air and improve production efficiency. Through closed space devices and degassing equipment, the degassing process can be accurately controlled to reduce the time and cost of degassing treatment. Placing or heating and curing at room temperature can promote the curing reaction of the refractory bulk material and improve the performance of the cured refractory layer. Through closed space devices and degassing equipment, gas emissions during the degassing process can be reduced and the impact on the environment can be reduced. Through the steps of preset proportion mixing, layered filling, vibration treatment, degassing treatment and curing treatment, the controllability and repeatability of the production process can be achieved to ensure the consistency of product quality. In summary, the present invention successfully prepares a cured refractory layer with good performance through a series of mixing, molding, drying, sintering, cooling, grinding, preparing refractory bulk materials, filling molds, vibration treatment, degassing treatment and curing treatment steps, and can meet the requirements of standard curing strength by adjusting vibration parameters or grinding power.

[0033] Furthermore, by testing the curing strength and pore area ratio of the cured refractory layer, the quality and reliability of the cured refractory layer can be ensured, thereby improving the overall performance of the product. If the actual curing strength is less than the standard curing strength, the curing strength can be improved by adjusting the vibration frequency, vibration duration, grinding power, etc. during the preparation process to meet the standard requirements. By promptly discovering and adjusting problems in the preparation process, material waste and production costs can be reduced, and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layers meets the same quality standards. The testing process of curing strength and pore area ratio helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0034] Furthermore, by comparing the actual pore area ratio with the standard pore area ratio range, it can be ensured that the product quality of the cured refractory layer meets the established standard requirements. According to the first curing strength comparison result, it can be determined whether it is necessary to adjust the grinding power, curing time, vibration parameters or vibration mode, so as to optimize the preparation process and improve the overall performance of the product. Through testing and comparison, problems in the production process can be discovered and solved in a timely manner, and the impact of uncertain factors on product quality can be reduced. By accurately adjusting the preparation process parameters, production efficiency can be improved and rework and waste caused by unqualified products can be reduced. By ensuring that the product meets the standards and has stable performance, the competitiveness of the product in the market can be enhanced. Through the detection and comparison of curing strength and pore area ratio, continuous improvement in the production process can be promoted, and the quality and performance of the product can be continuously improved.

[0035] Furthermore, by classifying the results of the compressive strength test, the quality of the cured refractory layer can be accurately controlled to ensure that each layer meets the predetermined standards. For the layered areas where the actual pore area ratio is less than or greater than the standard pore area ratio range, the process parameters such as grinding power, curing time, vibration parameters or vibration mode can be adjusted in time to improve the curing strength and ensure that the product meets the standards. By accurately controlling the quality and performance of the cured refractory layer, the performance of the product can be enhanced and its stability and reliability during use can be improved. By analyzing and processing the results of the compressive strength test, continuous improvement in the production process can be promoted, process parameters can be continuously optimized, and product quality can be improved. By meeting the curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured to meet the construction requirements.

[0036] Furthermore, by adjusting the grinding power or degassing time, the performance of the cured refractory layer can be improved so that it reaches a predetermined standard curing strength. According to the comparison results of the first actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layers meets the same quality standards. The testing process of curing strength and pore area ratio helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0037] Furthermore, by adjusting the vibration frequency, the performance of the cured refractory layer can be improved so that it reaches a predetermined standard curing strength. According to the comparison results of the second actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layers meets the same quality standards. The vibration frequency detection process helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0038] Furthermore, by increasing the vibration duration, the performance of the cured refractory layer can be improved so that it reaches a predetermined standard curing strength. According to the comparison results of the second actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By accurately adjusting the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of the cured refractory layer meets the same quality standards. The vibration duration detection process helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0039] Furthermore, by determining the bulk material first layer thickness and vibration duration according to the grinding particle size, the quality and uniformity of the refractory layer can be ensured, thereby improving the overall performance of the product. By accurately controlling the bulk material first layer thickness and vibration duration, the preparation process can be optimized and the overall performance of the product can be improved. By accurately controlling the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. The testing process of curing strength and pore area ratio helps to establish a quality control system.

[0040] Furthermore, by adjusting the vibration mode, the performance of the cured refractory layer can be improved to achieve a predetermined standard curing strength. According to the relationship between the curing strength and the vibration mode, the preparation process can be adjusted in time to improve the overall performance of the product. By accurately adjusting the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength required for the tundish construction, the performance and safety of the cured refractory layer in actual application can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of the cured refractory layer meets the same quality standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1It is a flow chart of the method for preparing the self-curing tundish dry material in the embodiment;

[0042] Figure 2 It is a flow chart of the degassing process of the method for preparing the self-curing tundish dry material in the embodiment;

[0043] Figure 3 It is a flow chart of the curing strength detection process of the method for preparing the self-curing tundish dry material in the embodiment;

[0044] Figure 4 It is a flow chart of the actual curing strength judgment process of the method for preparing the self-curing tundish dry material in the embodiment;

[0045] Figure 5 It is a flow chart of the filling process of the dry material in the tundish of the method for preparing the self-curing dry material in the tundish in the embodiment. DETAILED DESCRIPTION

[0046] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0047] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0048] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.

[0049] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0050] See also Figure 1-Figure 4 As shown, Figure 1 It is a flow chart of the method for preparing the self-curing tundish dry material in the embodiment; Figure 2It is a flow chart of the degassing process of the method for preparing the self-curing tundish dry material in the embodiment; Figure 3 It is a flow chart of the curing strength detection process of the method for preparing the self-curing tundish dry material in the embodiment; Figure 4 It is a flow chart of the actual curing strength judgment process of the method for preparing the self-curing tundish dry material in the embodiment; Figure 5 It is a flow chart of the filling process of the dry material in the tundish of the method for preparing the self-curing dry material in the tundish in the embodiment.

[0051] This embodiment provides a method for preparing a self-curing tundish dry material, comprising the following steps:

[0052] Step S1, mixing, molding, drying, sintering, cooling and grinding the tundish dry material raw materials to obtain tundish dry material bulk, and mixing the tundish dry material bulk and gel material according to a preset ratio to obtain refractory bulk;

[0053] Step S2, filling the refractory bulk material into the tundish mold, and adopting layered filling, vibrating each layer of the refractory bulk material to obtain a refractory solid material, degassing the refractory solid material to obtain a degassed refractory solid material, curing the degassed refractory solid material to obtain a cured refractory layer, and detecting the curing strength of the cured refractory layer to obtain an actual cured strength;

[0054] Step S3, when the actual curing strength cannot meet the standard curing strength requirement, adjusting the vibration parameters or adjusting the grinding power to meet the standard curing strength requirement;

[0055] The vibration parameters include vibration frequency and vibration duration.

[0056] Take a preset amount of tundish dry material raw materials, including bauxite, high aluminum powder, silicon powder, etc., and put them into a mixer for uniform mixing;

[0057] Molding: The mixed raw materials are fed into a ball press to obtain balls of a specified size;

[0058] Drying: Place the formed balls into a drying oven and dry them at 100-150°C for 4-6 hours to remove moisture from the balls.

[0059] Sintering: The dried balls are sent into a sintering furnace and sintered at a high temperature of 1300-1500℃ for 2-4 hours to enhance the strength and density of the balls;

[0060] Cooling: The sintered balls are naturally cooled to room temperature;

[0061] Grinding: Grind the cooled material balls through a grinder to obtain a bulk dry material of the intermediate package with a specified grinding particle size. The grinder includes but is not limited to a ball mill, a vibration mill and a jet mill, which are not specifically limited in this embodiment.

[0062] Preparation of refractory bulk material: the ground bulk material and gel material, which includes but is not limited to silicate gel, phosphate gel and aluminate gel, are put into a mixer according to a preset ratio, for example, the ratio of bulk material to gel material is 98:2, and are fully mixed to obtain refractory bulk material;

[0063] Among them, the gel material is a binder used to bond the refractory bulk materials together.

[0064] Filling the mold: Fill the refractory bulk material into the tundish mold in layers;

[0065] Vibration treatment: vibrate each layer of refractory bulk material to remove air and improve density;

[0066] Preferably, the refractory bulk material in the mold is vibrated by mechanical vibration.

[0067] Degassing treatment: Degassing treatment is performed on the vibrated refractory solid material to further remove the internal gas and obtain degassed refractory solid material.

[0068] The degassing process comprises the following steps:

[0069] Step S211, sealing the mold space where the refractory solid material is located after the vibration is completed, and the size of the device used for sealing the space is determined according to the size of the inner wall of the tundish;

[0070] Step S212, connecting the degassing device to the exhaust port reserved in the closed space device, and turning on the degassing device for degassing;

[0071] Step S213, after the degassing in the enclosed space is completed, the enclosed space device is opened.

[0072] Curing treatment: Place the degassed refractory solid material at room temperature for 24 hours, or heat and cure it at 60-80°C for 4-6 hours to obtain a cured refractory layer.

[0073] Through sintering and grinding operations, the particle size of the tundish dry bulk material is optimized, the contact area and connection strength between particles are increased, and thus the overall strength and durability of the refractory layer are enhanced. Layered filling and vibration treatment help to remove air from the refractory bulk material, reduce pores, and increase density, thereby improving the air tightness and thermal stability of the refractory layer. Vibrating the refractory bulk material in the mold by mechanical vibration can quickly and effectively remove air and improve production efficiency. Through closed space devices and degassing equipment, the degassing process can be accurately controlled to reduce the time and cost of degassing treatment. Placing or heating curing at room temperature can promote the curing reaction of the refractory bulk material and improve the performance of the cured refractory layer. Through closed space devices and degassing equipment, gas emissions during the degassing process can be reduced and the impact on the environment can be reduced. Through the steps of preset proportion mixing, layered filling, vibration treatment, degassing treatment and curing treatment, the controllability and repeatability of the production process can be achieved to ensure the consistency of product quality. In summary, the present invention successfully prepares a cured refractory layer with good performance through a series of mixing, molding, drying, sintering, cooling, grinding, preparing refractory bulk materials, filling molds, vibration treatment, degassing treatment and curing treatment steps, and can meet the requirements of standard curing strength by adjusting vibration parameters or grinding power.

[0074] Specifically, the process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes:

[0075] The curing strength of the cured refractory layer is tested by compressive strength test to obtain the actual curing strength. If the actual curing strength cannot be determined by a single test, the pore area on the surface of each layer of degassed refractory solid material is tested to obtain the actual pore area ratio of the degassed refractory solid material;

[0076] The actual pore area ratio is the ratio of the pore area in the detection area to the area of ​​the detection area.

[0077] Specifically, the process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes:

[0078] The actual pore area ratio of each layer of degassed refractory material is compared with the standard pore area ratio range to obtain a first area ratio comparison result, and the solidified refractory layer in the corresponding layered area is selected according to the first area ratio comparison result for a solidification strength test.

[0079] Randomly select several layered areas of the cured refractory layer for curing strength testing;

[0080] The process of curing strength detection includes the following steps:

[0081] Step S221, dividing the selected solidified refractory layer stratification area into a number of detection areas, and collecting the solidified refractory layer material in the detection area in a preset cubic shape to obtain a test sample;

[0082] Step S222, placing the sample on the platform of the pressure testing machine, and using the pressure testing machine to perform compressive strength tests on the cured refractory layer materials in the test area, wherein the compressive strength is the maximum pressure value that the test sample withstands when it is damaged;

[0083] Step S223, calculating the average of the compressive strengths in the layered area of ​​the solidified refractory layer, and the calculation result is the actual solidified strength.

[0084] If the actual curing strength of several cured refractory layers is greater than or equal to the standard curing strength, it is judged that the actual curing strength of the cured refractory layer meets the standard curing strength requirement, and there is no need to adjust the preparation process of the self-curing tundish dry material;

[0085] Wherein, the standard curing strength is obtained through the tundish construction requirements;

[0086] If any of the actual solidification strengths of several solidified refractory layers is less than the standard solidification strength, the pore area on the surface of each layer of refractory material is detected to obtain the actual pore area ratio of the refractory material;

[0087] The pores on the surface of each layer of refractory material are detected by a pore detection device, and the area of ​​the detection region and the area of ​​the pores within the detection region are recorded. The pore detection device can be a high-definition camera with data processing function or a high-definition camera connected to a computer, which is not specifically limited in this embodiment.

[0088] Determine the actual pore area ratio of the refractory material based on the area of ​​the test area and the pore area within the test area;

[0089] Compare the actual pore area ratio with the standard pore area ratio range to obtain a first area ratio comparison result,

[0090] In the case where the first area ratio comparison result shows that the actual pore area ratio is within the standard pore area ratio range, there is no need to detect the curing strength of the cured refractory layer in the corresponding layered area.

[0091] By testing the curing strength and pore area ratio of the cured refractory layer, the quality and reliability of the cured refractory layer can be ensured, thereby improving the overall performance of the product. If the actual curing strength is less than the standard curing strength, the curing strength can be improved by adjusting the vibration frequency, vibration duration, grinding power, etc. during the preparation process to meet the standard requirements. By timely discovering and adjusting problems in the preparation process, material waste and production costs can be reduced, and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of the cured refractory layer meets the same quality standards. The testing process of curing strength and pore area ratio helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0092] Specifically, the process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test according to the first area ratio comparison result includes:

[0093] If the first area ratio comparison result shows that the actual pore area ratio is not within the standard pore area ratio range, select the cured refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual cured strengths to be verified, compare the actual cured strengths to be verified with the standard cured strength range to obtain a first cured strength comparison result, and determine whether to adjust the grinding power, curing time, vibration parameters or vibration mode according to the first cured strength comparison result;

[0094] Wherein, the standard curing strength interval is determined according to the standard curing strength.

[0095] By comparing the actual pore area ratio with the standard pore area ratio range, it can be ensured that the product quality of the cured refractory layer meets the established standard requirements. According to the comparison results of the first curing strength, it can be determined whether it is necessary to adjust the grinding power, curing time, vibration parameters or vibration mode, so as to optimize the preparation process and improve the overall performance of the product. Through testing and comparison, problems in the production process can be discovered and solved in a timely manner, and the impact of uncertain factors on product quality can be reduced. By accurately adjusting the preparation process parameters, production efficiency can be improved and rework and waste caused by unqualified products can be reduced. By ensuring that the product meets the standards and has stable performance, the competitiveness of the product in the market can be enhanced. Through the detection and comparison of curing strength and pore area ratio, continuous improvement in the production process can be promoted and the quality and performance of the product can be continuously improved.

[0096] Specifically, according to the comparison result of the first area ratio, the solidified refractory layer in the corresponding layered area whose actual pore area ratio is not within the standard range is selected for compressive strength test.

[0097] The process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual solidified strengths to be verified includes:

[0098] For a stratified area where the actual pore area ratio is less than the minimum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified area to obtain a first actual cured strength to be verified;

[0099] For a stratified region where the actual pore area ratio is greater than the maximum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified region to obtain a second actual cured strength to be verified.

[0100] By classifying the results of the compressive strength test, the quality of the cured refractory layer can be accurately controlled to ensure that each layer meets the predetermined standards. For the layered areas where the actual pore area ratio is less than or greater than the standard pore area ratio range, the process parameters such as grinding power, curing time, vibration parameters or vibration mode can be adjusted in time to improve the curing strength and ensure that the product meets the standards. By accurately controlling the quality and performance of the cured refractory layer, the performance of the product can be enhanced and its stability and reliability during use can be improved. By analyzing and processing the results of the compressive strength test, continuous improvement in the production process can be promoted, process parameters can be continuously optimized, and product quality can be improved. By meeting the curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured to meet the construction requirements.

[0101] Specifically, the process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes:

[0102] Compare the first actual curing strength to be verified with the standard curing strength range. If the comparison result of the first curing strength is that the first actual curing strength to be verified is not within the standard curing strength range, increase the grinding power or reduce the degassing time to meet the standard curing strength requirement.

[0103] The first actual curing strength to be verified is the curing strength of the delamination area where the actual pore area ratio is less than the minimum value of the standard pore area ratio range,

[0104] If the first curing strength comparison result is that the first actual curing strength to be verified is within the standard curing strength range, there is no need to adjust the relevant parameters in the preparation process;

[0105] For the case where the first curing strength comparison result is that the first actual curing strength to be verified is less than the minimum value of the standard curing strength interval, the first actual curing strength to be verified is increased by increasing the grinding power, and the increased grinding power is determined according to the initial grinding power and the difference between the minimum value of the standard curing strength interval and the first actual curing strength to be verified, wherein the increased grinding power is positively correlated with the difference between the minimum value of the standard curing strength interval and the first actual curing strength to be verified, and the positive correlation ratio between the increased grinding power and the minimum value of the standard curing strength interval and the first actual curing strength to be verified is determined by a preset ratio influence compensation parameter;

[0106] For the case where the first curing strength comparison result is that the first actual curing strength to be verified is greater than the maximum value of the standard curing strength interval, the first actual curing strength to be verified is reduced by reducing the degassing time, and the reduced degassing time is determined according to the initial degassing time and the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval, wherein the reduced degassing time is negatively correlated with the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval, and the negative correlation ratio between the reduced degassing time and the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval is determined by a preset proportional influence compensation parameter;

[0107] The initial degassing time is the time recorded during degassing.

[0108] For example: Assuming the standard curing strength range is [5MPa, 10MPa],

[0109] Case 1: Comparing the first actual curing strength to be verified with the standard curing strength range, the measured first actual curing strength to be verified is 4MPa, and the actual pore area ratio is less than the minimum value of the standard pore area ratio range;

[0110] Increased grinding power = initial grinding power + K × difference between the minimum value of the standard pore area ratio range and the actual pore area ratio, where K is the negative correlation ratio affecting the compensation parameter between the reduced degassing time and the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval,

[0111] Assuming the initial grinding power is 2kW, the increased grinding power = 2kW + 0.5kW / MPa × 1MPa = 2.5kW;

[0112] Case 2: The actual curing strength of the first to be verified is 12MPa, which is higher than the maximum value of the standard curing strength range of 10MPa.

[0113] Determine that the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval is 2MPa,

[0114] The reduced degassing time = initial degassing time - m × the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval, where m is the negative correlation ratio between the reduced degassing time and the difference between the first actual curing strength to be verified and the maximum value of the standard curing strength interval, affecting the compensation parameter.

[0115] Assuming that the initial degassing time is 10 minutes, the reduced degassing time = 10 minutes - 1 minute / MPa × 2 MPa = 8 minutes, where the initial degassing time is the time recorded after the degassing is completed.

[0116] By adjusting the grinding power or degassing time, the performance of the cured refractory layer can be improved to reach the predetermined standard curing strength. According to the comparison results of the first actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layers meets the same quality standards. The testing process of curing strength and pore area ratio helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0117] Specifically, the process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes:

[0118] The second actual curing strength to be verified is compared with the standard curing strength interval. If the comparison result of the first curing strength is that the second actual curing strength to be verified is not within the standard curing strength interval, the vibration frequency is adjusted to meet the standard curing strength requirement.

[0119] If the first curing strength comparison result is that the second actual curing strength to be verified is within the standard curing strength range, there is no need to adjust the relevant parameters in the preparation process;

[0120] For the case where the comparison result of the first curing strength is that the second actual curing strength to be verified is less than the minimum value of the standard curing strength interval, the vibration frequency is increased to increase the second actual curing strength to be verified, and the increased vibration frequency is determined according to the initial vibration frequency and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, wherein the increased vibration frequency is positively correlated with the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, and the positive correlation ratio between the increased vibration frequency and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified is determined by a preset proportional influence compensation parameter.

[0121] For the case where the comparison result of the first curing strength is that the second actual curing strength to be verified is greater than the maximum value of the standard curing strength interval, since the second actual curing strength to be verified is the stratified area where the actual pore area ratio is greater than the maximum value of the standard pore area ratio range, it can be understood that the more pores on the surface of the cured refractory layer material, the larger the actual pore area ratio and the lower the curing strength, so the case where the actual pore area ratio is greater than the maximum value of the standard pore area ratio range is not discussed.

[0122] For example: Assuming the standard curing strength range is still [5MPa, 10MPa],

[0123] Case 1: The actual curing strength of the second to be verified was measured to be 4.5MPa.

[0124] The difference between the actual curing strength to be verified and the minimum value of the standard curing strength interval is 0.5MPa;

[0125] The increased vibration frequency = initial vibration frequency + n × the difference between the second actual curing strength to be verified and the minimum value of the standard curing strength interval. Assuming that the initial vibration frequency is 20Hz, n is the positive correlation ratio between the increased vibration frequency and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, which affects the compensation parameter. According to the experimental data, the value of n is determined to be 10Hz / MPa.

[0126] Increased vibration frequency = 20Hz + 10Hz / MPa × 0.5MPa = 20Hz + 5Hz = 25Hz;

[0127] Case 2: The second actual curing strength to be verified is measured to be 8 MPa. By comparing the second actual curing strength to be verified with the standard curing strength range, since 8 MPa is within the range of [5 MPa, 10 MPa], there is no need to adjust the relevant parameters in the preparation process.

[0128] By adjusting the vibration frequency, the performance of the cured refractory layer can be improved to reach the predetermined standard curing strength. According to the comparison results of the second actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By meeting the standard curing strength required for the tundish construction, the performance and safety of the cured refractory layer in actual application can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layer meets the same quality standards. The vibration frequency detection process helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0129] Specifically, the process of adjusting the vibration frequency to meet the standard curing strength requirements includes:

[0130] If the vibration frequency cannot meet the standard curing strength requirement, the vibration duration can be adjusted to meet the standard curing strength requirement.

[0131] For the case where the comparison result of the first curing strength is that the second actual curing strength to be verified is less than the minimum value of the standard curing strength interval, the second actual curing strength to be verified is increased by increasing the vibration duration, and the increased vibration duration is determined according to the initial vibration frequency and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, wherein the increased vibration duration is positively correlated with the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, and the positive correlation ratio between the increased vibration duration and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified is determined by a preset proportional influence compensation parameter.

[0132] The difference between the second actual curing strength to be verified and the minimum value of the standard curing strength interval = the minimum value of the standard curing strength interval - the second actual curing strength to be verified = 5MPa-4.5MPa = 0.5MPa

[0133] The increased vibration duration = initial vibration duration + p × the difference between the second actual curing strength to be verified and the minimum value of the standard curing strength interval, p is the positive correlation ratio between the increased vibration duration and the difference between the minimum value of the standard curing strength interval and the second actual curing strength to be verified, affecting the compensation parameter;

[0134] The increased vibration duration = 60 seconds + 120 seconds / MPa × 0.5 MPa == 120 seconds, where it is assumed that the initial vibration duration is 60 seconds.

[0135] By increasing the vibration duration, the performance of the cured refractory layer can be improved so that it reaches the predetermined standard curing strength. According to the comparison results of the second actual curing strength to be verified and the standard curing strength interval, the preparation process can be adjusted in time to improve the overall performance of the product. By accurately adjusting the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual applications can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of the cured refractory layer meets the same quality standards. The vibration duration detection process helps to establish a quality control system, promote continuous improvement, and improve the quality management level of the overall production process.

[0136] Specifically, the process of filling the refractory bulk material into the tundish mold and adopting layered filling includes:

[0137] The thickness of the first layer of the filling bulk material is determined according to the grinding particle size of the dry bulk material in the tundish, and the vibration duration is determined according to the thickness of the first layer of the bulk material.

[0138] Determine the thickness of the first layer of bulk material according to the grinding particle size. The thickness of the first layer of bulk material is positively correlated with the grinding particle size. The positive correlation ratio between the thickness of the first layer of bulk material and the grinding particle size is determined according to the material properties and the mold size.

[0139] First layer thickness = K × grinding particle size, where K is the positive correlation coefficient between the first layer thickness of bulk material and the grinding particle size.

[0140] The vibration duration is determined according to the thickness of the first layer of bulk material. The vibration duration is positively correlated with the thickness of the first layer of bulk material.

[0141] The tundish dry material filling process includes the following steps:

[0142] Step S231, prepare the tundish mold and ensure that its interior is clean and dry;

[0143] Step S232, using appropriate tools, evenly fill the refractory bulk material into the mold, ensuring that the thickness of the first layer is about 10 mm;

[0144] Step S233, start the vibration equipment, and set the vibration time to 9.5 seconds to compact the first layer of bulk materials;

[0145] Step S234, after completing the first layer of vibration, continue to fill the next layer of bulk material and repeat the vibration process until the mold is filled.

[0146] By determining the bulk material first layer thickness and vibration duration according to the grinding particle size, the quality and uniformity of the refractory layer can be ensured, thereby improving the overall performance of the product. By accurately controlling the bulk material first layer thickness and vibration duration, the preparation process can be optimized and the overall performance of the product can be improved. By accurately controlling the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength requirements of the tundish construction, the performance and safety of the cured refractory layer in actual application can be ensured. The testing process of curing strength and pore area ratio helps to establish a quality control system.

[0147] Specifically, processes where adjusting the vibration frequency does not meet the standard curing strength requirements include:

[0148] While keeping the vibration frequency unchanged, adjust the vibration mode to meet the standard curing strength requirements;

[0149] Wherein, the vibration mode includes vertical vibration and horizontal vibration.

[0150] Assuming the vibration frequency is 25 Hz, the measured curing strength is 4.5 MPa, which is lower than the minimum value of the standard curing strength range;

[0151] Vibration modes include vertical vibration and horizontal vibration. Vertical vibration means that the direction of the vibration force is perpendicular to the working plane, and horizontal vibration means that the direction of the vibration force is parallel to the working plane.

[0152] Keeping the vibration frequency unchanged, switch the vibration device from horizontal vibration mode to vertical vibration mode.

[0153] The refractory bulk materials are vertically vibrated, which can help the materials to be better compacted, thereby improving the solidification strength.

[0154] If the vertical vibration fails to achieve the expected curing strength, keep the vibration frequency unchanged, switch the vibration equipment back to the horizontal vibration mode, and vibrate the refractory bulk material horizontally.

[0155] Horizontal vibration helps to evenly distribute the material in the mold, reducing air holes and thus improving the cured strength.

[0156] Based on the experimental results, the optimal vibration mode and parameter settings are determined to ensure that the curing strength meets the standard requirements.

[0157] By adjusting the vibration mode, the performance of the cured refractory layer can be improved to achieve the predetermined standard curing strength. According to the relationship between curing strength and vibration mode, the preparation process can be adjusted in time to improve the overall performance of the product. By accurately adjusting the preparation process parameters, material waste and production costs can be reduced and production efficiency can be improved. By meeting the standard curing strength required for tundish construction, the performance and safety of the cured refractory layer in actual application can be ensured. Through testing and adjustment, the consistency of the product can be improved to ensure that each batch of cured refractory layer meets the same quality standards.

[0158] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-curing tundish dry material, characterized in that: The following steps are included: The tundish dry material raw materials are mixed, formed, dried, sintered, cooled and ground to obtain tundish dry material bulk, and the tundish dry material bulk and gel material are mixed according to a preset ratio to obtain refractory bulk; Filling the refractory bulk material into a tundish mold, and adopting layered filling, vibrating each layer of the refractory bulk material to obtain a refractory solid material, degassing the refractory solid material to obtain a degassed refractory solid material, curing the degassed refractory solid material to obtain a cured refractory layer, and detecting the curing strength of the cured refractory layer to obtain an actual cured strength; In the case where the actual curing strength cannot meet the standard curing strength requirement, the standard curing strength requirement is met by adjusting the vibration parameters or the grinding power; The vibration parameters include vibration frequency and vibration duration.

2. The method for preparing the self-curing tundish dry material according to claim 1, characterized in that: The process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes: The curing strength of the cured refractory layer is tested by compressive strength test to obtain the actual curing strength. If the actual curing strength cannot be determined by a single test, the pore area on the surface of each layer of degassed refractory solid material is tested to obtain the actual pore area ratio of the degassed refractory solid material; The actual pore area ratio is the ratio of the pore area in the detection area to the area of ​​the detection area.

3. The method for preparing the self-curing tundish dry material according to claim 2, characterized in that: The process of detecting the curing strength of the cured refractory layer to obtain the actual curing strength includes: The actual pore area ratio of each layer of degassed refractory material is compared with the standard pore area ratio range to obtain a first area ratio comparison result, and the solidified refractory layer in the corresponding layered area is selected according to the first area ratio comparison result for a solidification strength test.

4. The method for preparing the self-curing tundish dry material according to claim 3, characterized in that: The process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test according to the first area ratio comparison result includes: If the first area ratio comparison result shows that the actual pore area ratio is not within the standard pore area ratio range, select the cured refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual cured strengths to be verified, compare the actual cured strengths to be verified with the standard cured strength range to obtain a first cured strength comparison result, and determine whether to adjust the grinding power, curing time, vibration parameters or vibration mode according to the first cured strength comparison result; Wherein, the standard curing strength interval is determined according to the standard curing strength.

5. The method for preparing the self-curing tundish dry material according to claim 4, characterized in that: The process of selecting the solidified refractory layer in the corresponding layered area for compressive strength test to obtain a number of actual solidified strengths to be verified includes: For stratified regions where the actual pore area ratio is less than the minimum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified region to obtain a first actual cured strength to be verified; for stratified regions where the actual pore area ratio is greater than the maximum value of the standard pore area ratio range, a compressive strength test is performed on the cured refractory layer in the stratified region to obtain a second actual cured strength to be verified.

6. The method for preparing the self-curing tundish dry material according to claim 5, characterized in that: The process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes: Compare the first actual curing strength to be verified with the standard curing strength range. If the comparison result of the first curing strength is that the first actual curing strength to be verified is not within the standard curing strength range, increase the grinding power or reduce the degassing time to meet the standard curing strength requirement.

7. The method for preparing the self-curing tundish dry material according to claim 6, characterized in that: The process of comparing the actual curing strength to be verified with the standard curing strength interval to obtain a first curing strength comparison result includes: The second actual curing strength to be verified is compared with the standard curing strength interval. If the comparison result of the first curing strength is that the second actual curing strength to be verified is not within the standard curing strength interval, the vibration frequency is adjusted to meet the standard curing strength requirement.

8. The method for preparing the self-curing tundish dry material according to claim 7, characterized in that: The process of adjusting the vibration frequency to meet the standard curing strength requirements includes: If the vibration frequency cannot meet the standard curing strength requirement, the vibration duration can be adjusted to meet the standard curing strength requirement.

9. The method for preparing the self-curing tundish dry material according to claim 8, characterized in that: The process of filling the refractory bulk material into the tundish mold and filling in layers includes: The thickness of the first layer of the filling bulk material is determined according to the grinding particle size of the dry bulk material in the tundish, and the vibration duration is determined according to the thickness of the first layer of the bulk material.

10. The method for preparing the self-curing tundish dry material according to claim 9, characterized in that: Processes where adjusting the vibration frequency does not meet the standard curing strength requirements include: While keeping the vibration frequency unchanged, adjust the vibration mode to meet the standard curing strength requirements; Wherein, the vibration mode includes vertical vibration and horizontal vibration.

Citation Information

Patent Citations

  • Tundish environment-friendly dry material and preparation method thereof

    CN117776699A

  • Quantitative evaluation method for apparent mass of fair-faced concrete

    CN110349123A

  • Detection method for compressive strength of foam concrete

    CN111060440A

  • Heat-preservation refractory castable as well as preparation method, pouring method and application thereof

    CN111704473A

  • Self-curing dry material for tundish and preparation method thereof

    CN112341216A

Cited By

  • High-performance continuous casting tundish dry material forming method

    CN119910741A